PENDIDIKAN BERBASIS MUTU: Reorientasi Manajemen Pendidikan di Negara Berkembang - Yeni Trinur Rahmawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2014)
In order to address the challenge of globalization era, the world of education should rectify its quality. In order to attain the good quality for developing countries. The education caretaker or school has to own an internal and external client. Standard quality education ought to run simultananesously thorugh some steps such as: non quality assurance, and integrated quality management. However, the principals of quality are focused on the client, total involvement, measurement, commitment, and continuous restoration. The step of the implementation of the principals of quality, as the theory developed by management countries developing are creating the purpose consistency, adopt the total quality management philosopy, diminish the testing need, appraise school business with new procedure, repair the quality, life long learning for all people. By doing step, the implementation quality management in developing countries can be achieved and it is suited with the purpose desired, as what has been done in developing countries.